THE URGENCY OF DIVINE PRINCIPLES IN THE IMPLENTATION OF ARBITRATION AWARD EXECUTION IN INDONESIA - huzaimah al anshori; Sapto Hadi Pamungkas; Aklis Mukhidin; M. Syamsudin (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Divine Principles Application in Resolving Business Disputes at the Indonesian National Arbitration Board (BANI) Surabaya. It is important to note that some parties involved in arbitration disputes do not comply with arbitration decisions in Indonesia. Consequently, they resort to measures such as filing annulment requests in the District Court and escalating the matter to the Commercial Court. This situation highlights the urgent need for applying divine principles in executing arbitration awards in Indonesia. The question arises: how do divine principles function in executing national arbitration awards in Indonesia. The author undertakes empirical research utilizing socio-legal approaches, case study approaches, conceptual approaches, and philosophical approaches. To provide solutions for the execution of arbitration awards in Indonesia, various theories are employed, including Grundnorm theory, the theory of legal consciousness and compliance, natural law theory, and the theory of pacta sunt servanda. The principle of divinity, as reflected in the preamble of decisions stating "For Justice Based on the Almighty God," necessitates a sincere intention from the disputing parties to comply with and adhere to the arbitration decision. Furthermore, the parties are encouraged to seek common ground for the greater good (maslahah), aligning with Imam Shatibi's theory of maslahah, which posits that where there is benefit, there is divine law. Implementing National Arbitration award execution can be voluntarily carried out by applying the Divine Principle, as demonstrated by the cases involving PT. Nugraha Adi Taruna as the contractor with the Kediri City Government/Public Works Agency/Head of Procurement Services, and the contractor PT. Murni Construction with the Kediri City Government/Public Works Agency/Head of Procurement Services. The effective application of the Divine Principle in the preamble of decisions rendered by the arbitral tribunal and the execution of arbitration awards requires the intent of the parties, advice from their legal counsel, and direction from the head of the District Court. Theoretically, the operation of the Divine Principle is facilitated through pacta sunt servanda, the theory of legal consciousness and compliance, natural law theory, and Grundnorm theory. Keywords: Urgency of Divine Principles, Execution, Arbitration Awards